1998
DOI: 10.1515/hfsg.1998.52.4.405
|View full text |Cite
|
Sign up to set email alerts
|

Chemimechanical Pulping of Poplar Wood. Alkaline Wood Pretreatment at Low Temperature

Abstract: The low temperature alkaline treatment of Cottonwood (Populus deltoides) was studied by applying a factorial experimental design. The effects of treatment time and alkali concentration on alkali consumption, as well as treatment yield, carboxyl groups and acetyl groups contents were investigated. Relationships between these contents and wood swelling measured by the water retention value (WRV) were also analyzed. In the whole alkali-concentration range under study, the deacetylation process was responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The deacetylation increases the ion exchange capacity of wood (Sjöström et al 1965), which is also manifested by an improved enzymatic hydrolysis due to the higher accessibility of the polysaccharide structures to enzymes (Kong et al 1992). The water retention ability of wood meal also increases with increasing degrees of deacetylation (Zanuttini et al 1998). Inalbon et al (2009) demonstrated that deacetylation contributes a lot to wood swelling.…”
Section: Introductionmentioning
confidence: 98%
“…The deacetylation increases the ion exchange capacity of wood (Sjöström et al 1965), which is also manifested by an improved enzymatic hydrolysis due to the higher accessibility of the polysaccharide structures to enzymes (Kong et al 1992). The water retention ability of wood meal also increases with increasing degrees of deacetylation (Zanuttini et al 1998). Inalbon et al (2009) demonstrated that deacetylation contributes a lot to wood swelling.…”
Section: Introductionmentioning
confidence: 98%
“…Degree of change is dependent on time, temperature and alkali concentration [7,8]. Because of that, the aim of this paper was to investigate the influence of alkali pretreatment of softwood sawdust on their adsorption abilities.…”
Section: Introductionmentioning
confidence: 99%
“…An overall lowering of pH was observed during extraction except for sample A ( Table 2). The decrease in pH is explained by the release of acetic acid formed due to cleavage of acetyl pendant groups present on the hemicellulose backbone (Sjöström, Janson, Haglund, & Enström, 1965;Zanuttini, Citroni, Martínez, & Marzocchi, 1998). The yield was calculated as the amount of freeze-dried material obtained divided by the amount of dry weight straw charged.…”
Section: Evaluation Of the Extraction Conditionsmentioning
confidence: 99%
“…1) has been assigned to acetyl groups that have been cleaved from the chain due to deacetylation (Lundqvist et al, 2002;Teleman, Tenkanen, Jacobs, & Dahlman, 2002; Teleman, Lundqvist, Tjerneld, Stålbrand, Höije et al, 2005;Xu et al, 2010), and the signal is especially strong for extracts D and H which can be explained by higher degrees of deacetylation of hemicelluloses extracted under alkaline conditions. Sjöström et al (1965) and Zanuttini et al (1998) have demonstrated that during impregnation of wood in alkaline medium, deacetylation increases with increasing alkali. The mechanism of deacetylation during the extraction of oil-rapeseed straw should be similar to the deacetylation during impregnation in wood.…”
Section: Structural and Compositional Analysis Of Extracted Hemicellumentioning
confidence: 99%